PERANAN DINAS KEBUDAYAAN DAN PARIWISATA DALAM PENGEMBANGAN OBJEK WISATA DI KABUPATEN KEPULAUAN SANGIHE - HAMEL, ALVINITA; Ogotan, Martha; Tulusan, Femmy (Sam Ratulangi University, 2017)
ABSTRACTLocated in the northernmost position of Indonesia and adjacent to neighboring Philippines, Sangihe regency store tourism potential with a million charms but some promising potential tourist attraction is still not getting more attention from the local government, especially the Department of Culture and Tourism of the District of Sangihe Islands so can not yet Attracting as many foreign and dosmetic tourists as possible to visit theÂ area.In the preparation of this study the authors use Descriptive Research Methods intended to obtain information on the Development of Tourism Objects in the Department of Culture and Tourism District of Sangihe Islands. As for the informants in this study is the informant that has relevance to the problem and focus of research studied.Based on the result of research that role of culture and tourism in developing tourism object based on three indicator that is coordinator, facilitator, stimulator and there are some efforts done by Department of Culture and Tourism in developing tourism object that is Provision of Master Plan of Tourism Development Area, Culture and Tourism Department do cooperation between Government agencies, the Government in collaboration with the private sector in managing attractions, Human Resources DevelopmentÂ tour. Keywords: Role, Object of Tourism Development